“Perfect Hearts and Pure Pages”: The Transmission and Recitation of the Qur’an in Mamluk Cairo—the Shāṭibiyya as a Case Study - Hearn, Jonathan (AUC Knowledge Fountain, 2025)
The Ḥirz al-Amānī wa-Wajh al-Tahānī of Abū al-Qāsim b. Fīrruh al-Shāṭibī (d. 590/1193) became one of the most widely studied texts associated with the recitation of the Qur’an. A didactic versification of Abū ʿAmr al-Dānī’s (d. 444/1053) Kitāb al-Taysīr fī al-Qirāʾāt al-Sabaʿ, the Shāṭibiyya was composed in Ayyubid Egypt and transformed the discipline of the variant readings (qirāʾāt). Despite its popularity and acknowledged impact upon the discipline, the Shāṭibiyya remains a relatively untapped resource for understanding the Qur’an in its recited form. This thesis studies the recitation of the Qur’an in Mamluk Cairo through the Shāṭibiyya, using the didactic poem as a methodological fulcrum to analyse the texts, networks, and institutions to which it gave shape. Situating the Shāṭibiyya’s reception in the context of the sonic turn in Qur’anic and Islamic Studies and the debates surrounding an embodied epistemology in Islam, this thesis argues that the Shāṭibiyya and the discipline of the qirāʾāt were vital spheres of meaning-making for premodern Muslims. The highly-technical discourse of the Shāṭibiyya fashioned bearers of the Qur’an able to sonically reproduce the Qur’an in the various spaces and institutions of Mamluk Cairo. By analysing a range of adjacent texts, such as Ibn al-Jazarī’s (d. 833/1429) biographical dictionary of Qur’an reciters and Aḥmad al-Qas‏ṭallānī’s (d. 923/1517) work of manāqib on al-Shāṭibī, combined with the study of waqfiyyas and Qur’anic inscriptions, this thesis presents a novel approach to the study of the Shāṭibiyya, contributing to the growing literature that emphasises the significance of the recited Qur’an.